Properties of homogenous muf particleboard from bamboo (gigantochloa scortechinil) / Jamaludin Kasim and Abdul Jalil Ahmad - Kasim, Jamaludin; Ahmad, Abdul Jalil (2003)
In the study of high moisture resistant particleboard from bamboo (Gigantochloa scortechinii), homogenous melamine urea formaldehyde particleboard was produced. For homogenous board, increase in resin content was accompanied by an increase in the mechanical and improvement in water absorption and thickness swelling properties. Varying the particle sizes also showed differences in the mechanical and physical properties. Wax increased the water resistance of the board but decreased the mechanical properties. All boards surpassed the minimum requirement of the BS for the mechanical and physical properties. Particles from three-year-old Gigantochloa scortechinii was found to be suitable for the making of homogenous melamine urea formaldehyde particleboard.